IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK DALAM PENANGANAN TINDAK KEKERASAN ANAK DI KOTA SEMARANG - Bramanda Raihan Revario; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The number of cases of child violence in the city of Semarang is quite high in the last three years and the highest in the province of Central Java. Departing from these problems, this study aims to analyze the implementation of child protection policies in the city of Semarang along with the driving and inhibiting factors. This research uses descriptive qualitative method with purposive technique. The results of the study show that the implementation of the policy is successful in the process perspective, meaning that it is in accordance with the Regional Regulation of the City of Semarang Number 5 of 2016. The implementation of the policy has not been successful in the outcome perspective. This means that not all programs have succeeded in achieving policy objectives. The driving factors for policy implementation are supporting resources, the establishment of cooperation with other agencies, the existence of a routine agenda for program implementation, the existence of policy standards and objectives, and a supportive disposition. The inhibiting factors for policy implementation are the economic, social and cultural environment that exists in the community, there is an unsupportive disposition, the unavailability of rehab home infrastructure for cases of child violence, the unavailability of emergency funds to meet the needs of victims. DP3A and LPPPA Semarang City should maximize the use of social media as a medium to socialize and conduct training to rehab homes in Semarang City regarding handling victims of child violence, especially sexual violence.